Raciocínio lógico como recurso metodológico e o legado da avaliação do PISA - Silvestrini, Luiz Henrique da Cruz [UNESP]; Soares, Marcelo Reicher [UNESP]; Boato, Luis Felipe Salvador [UNESP]; Dua, Alessa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The results released by the Programme for International Student Assessment (PISA), in the edition of 2012, have culminated in the negative emphasis on the logical reasoning of Brazilian students, who apparently reason linearly, without being able to infer from minimal abstractions. On this environment, we establish research fronts linked to the Extension Project entitled "logical reasoning, analytical and quantitative: a tool for rational inclusion" by the Department of Mathematics, School of Sciences from UNESP, Bauru campus. In this presentation, we show how the acquisition of logical reasoning elements, be it analytical or quantitative, previously acquired, can contribute to the student's ability to solve logical/mathematical problems applied to real life.

Os resultados divulgados pelo Programa Internacional de Avaliação de Alunos (PISA), na edição de 2012, culminaram no destaque negativo para o raciocínio lógico dos estudantes brasileiros, os quais, aparentemente, raciocinam de forma linear, sem ser capazes de inferir a partir de abstrações mínimas. A partir deste panorama, pudemos estabelecer frentes de investigação vinculadas ao Projeto de Extensão “Raciocínio lógico, analítico e quantitativo: uma ferramenta para a inclusão racional” realizado pelo Departamento de Matemática da Faculdade de Ciências da UNESP, campus de Bauru. Nesta apresentação, mostramos como a aquisição de elementos de raciocínio lógico analítico e quantitativo, previamente adquiridos, podem contribuir na capacidade do aluno em resolver problemas lógicos/matemáticos aplicados à vida real.
Keywords: Logical reasoning; Mathematical language; PISA programme; Raciocínio lógico; Linguagem matemática; Avaliação PISA